What Do We Know About Interventions to Increase Women’s Economic Participation and Empowerment in South Asia? - World Bank (World Bank, Washington, DC, 2021)
The World Bank’s South Asia Region Gender Innovation Lab is conducting a systematic review and meta-analysis of interventions with direct or indirect effects on measures of women’s economic empowerment. The review focuses on changes in labor force participation, employment, income, and empowerment outcomes. The goal is to document what has worked and has not for women in the region (covering all countries; Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka), the types of interventions implemented, and identifiable gaps in knowledge and action. The review organizes interventions in six broad categories: skills, assets, credit, labor market, entrepreneurship, and empowerment. This note summarizes the main findings from skill-building interventions.